ANALISIS KINERJA MESIN CREPER LINE A DENGAN METODE OVERALL EQUIPMENT EFFECTIVENESS (OEE) DI PT BATANGHARI TEMBESI - Prima Fithri; Anjar Noer Said; Ismail Kurnia (Sekolah Tinggi Teknologi Industri Padang, 2020)
PT Batanghari Tembesi is a company that produces crumb rubber which will later be exported to various foreign companies. In the production process will not be separated from problems related to the effectiveness of the machine / equipment. Machines often experience damage or interference that can lead to wasted production time and decreased production levels. Therefore, effective and efficient steps in maintaining machinery / equipment are needed to overcome and prevent these problems. Overall Equipment Effectiveness (OEE) is a method of measuring the performance and effectiveness of machines / equipment used in the production process. In this OEE method there are three elements that are measured, namely Availability, Perfomance Rate, and Quality Rate. The object examined in this study is the PT Batanghari Tembesi creper line A machine because this machine is the most frequently damaged. Based on the calculation results, obtained the OEE value on the creper machine line A is 86.01%. Availabilty on the creper line A machine is 94.45%. Performance Efficiency on the creper line A machine is 91.05%, and the Quality Rate is 100%. Based on the analysis of observations there are four main factors that influence the performance and effectiveness of the machine, namely humans who are less careful and have not followed work procedures properly, machines that have not been properly treated, work methods that have not applied inspections of materials that will enter the production process and the environment (external), which is a power outage that makes the engine stop operating. While for the calculation of the value of each factor of the six big losses, it is found that the two biggest dominant factors (affecting the level of machine effectiveness) are breakdown time and reduced speed losses.